A comparison of physically and chemically defective graphene nanosheets as catalyst supports for cubic Pd nanoparticles in an alkaline oxygen reduction reaction. (20th December 2015) - Liu, Zhe-Ting; Huang, Kun-Lung; Wu, Yi-Shan; Lyu, Yuan-Ping; Lee, Chien-Liang
Graphical abstract: Abstract: An electrostatic attraction method is utilized for successfully attaching 10 nm Pd nanocubes on reduced graphene nanosheet (RGN) surfaces. The RGNs used to support the Pd nanocubes are prepared via both a sonoelectrochemical method (RGNSECM ) and a chemical reduction method (RGNCM ). X-ray photoelectron spectroscopic analyses indicate the domination of physical defects and C-OH groups on the surfaces of RGNSECM and RGNCM, respectively. The linear scanning voltammograms, taken using rotating ring-disk electrode analyses in alkaline oxidation-reduction reactions (ORRs), show that the Pd nanocubes supported by RGNSECM (Pd cubes/RGNSECM ) and RGNCM (Pd cubes/RGNCM ) show improved onset potentials of 0.1 V on the order of Pd cubes/RGNSECM  > Pd cubes/RGNCM  > Pt/C ∼ Pd/C > Pd nanocubes for their catalytic disk currents in the electron-transfer region. Mass-transfer-corrected Tafel diagrams demonstrate that RGNSECM, which contains a greater number of physical defects, facilitated greater active sites of these Pd nanocubes due to its greater surface area, and thus better promoted ORRs. In terms of the kinetic current density, a greater mass activity (7.85 × 10 −2  mA·μg −1 ) is observed for the Pd cubes/RGNSECM composite. Additionally, the durability test reveals that RGNSECM could provide good strength to stabilize Pd nanocubes during a long ORR period.